2019
DOI: 10.2807/1560-7917.es.2019.24.35.1800589
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis and taeniasis cases diagnosed at two referral medical institutions, Belgium, 1990 to 2015

Abstract: Background Few case reports on human infections with the beef tapeworm Taenia saginata and the pork tapeworm, Taenia solium , diagnosed in Belgium have been published, yet the grey literature suggests a higher number of cases. Aim To identify and describe cases of taeniasis and cysticercosis diagnosed at two Belgian referral medical institutions from 1990 to 2015. Methods In this observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A few cases of neurocysticercosis (NCC), the infection with the cystic larvae of Taenia solium in the brain, meninges, and spinal cord, were described, but there was no systematic screening for the disease. 20,48,49 Echinococcosis. Echinococcosis, or hydatid disease (caused by Echinococcus granulosus), was only reported very sporadically in migrants from SSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few cases of neurocysticercosis (NCC), the infection with the cystic larvae of Taenia solium in the brain, meninges, and spinal cord, were described, but there was no systematic screening for the disease. 20,48,49 Echinococcosis. Echinococcosis, or hydatid disease (caused by Echinococcus granulosus), was only reported very sporadically in migrants from SSA.…”
Section: Resultsmentioning
confidence: 99%
“…62 Unfortunately, in most of the studies, it was not clear whether the pathogen found in the stool was T. solium or T. saginata, because ova are indistinguishable in standard microscopy. 49,63,64 Hookworm, T. trichiura and A. lumbricoides, were found more commonly, but they often produce little morbidity. They also have a limited life span, so their prevalence decreases with the length of stay in the host country, and transmission is interrupted because of better hygienic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system infection in humans occurs when the individual accidentally ingests Taenia solium eggs, or when the larval stage has an affinity for the central nervous system tissue, causing NC [3]. NC can present several clinical manifestations according to the type, quantity and location of cysticerci in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…NC can present several clinical manifestations according to the type, quantity and location of cysticerci in the nervous system. Common clinical manifestations of NC include epileptic seizures, cysticercotic meningitis, dementia, obstructive hydrocephalus and, more rarely, parkinsonism [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no gastroenterological association endorses guidelines on the diagnostic approach of suspected intestinal helminthic infections based on the clinical presentation and/or an individual's migration history. common species with a cosmopolitan distribution, which are therefore endemic in the Western world, are Echinococcus (especially multilocularis), Entero-bius, Toxocara, Trichinella and Taenia (12)(13)(14)(15)(16).…”
Section: Epidemiologymentioning
confidence: 99%